Multi-scale three-dimensional network carbon skeleton structure auxiliary composite material and preparation method thereof

By introducing a multi-scale three-dimensional network carbon framework structure into the composite material, the problem of oxidation and filling of composite materials in high-temperature environments is solved, the refinement and ablation performance of ceramic particles are improved, and high-performance ceramic modified materials are formed.

CN119263864AActive Publication Date: 2025-01-07NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411469630.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-07
Estimated Expiration
2044-10-21

Smart Images

  • Figure CN119263864A_ABST
    Figure CN119263864A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite material preparation, and discloses a multi-scale three-dimensional network carbon skeleton structure auxiliary composite material and a preparation method thereof. The preparation method comprises the following steps: impregnating a low-density fiber preform composite material in a precursor solution to obtain an impregnated low-density fiber preform composite material; the precursor solution is a mixed solution of resorcinol, a formaldehyde solution, distilled water and hexadecyl trimethyl ammonium bromide; and carrying out curing treatment, carbonization treatment and active reaction infiltration treatment on the impregnated low-density fiber preform composite material to obtain the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material. A three-dimensional network carbon skeleton structure is introduced into a low-density preform composite material, macropores are effectively divided, the capillary action is enhanced, meanwhile, molten alloy is fully reacted, residual metal in the composite material is reduced, and the grain size of a ceramic product is refined, so that the high-performance ceramic modified composite material is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and relates to a multi-scale three-dimensional network carbon skeleton structure auxiliary composite material and a preparation method thereof. Background Art

[0002] Carbon / carbon composites are widely used in thermal protection components of aerospace vehicles due to their low density, high specific strength, high modulus and excellent high-temperature mechanical properties. However, they will oxidize in an oxygen environment above 400 °C, which can easily cause the material to fail prematurely due to structural instability. Therefore, ultra-high temperature ceramic components (such as HfC, ZrC, HfB2, ZrB2, etc.) are usually used for modification to improve their anti-oxidation / ablation properties. Among them, reactive melt infiltration technology (RMI) has become the preferred method due to its advantages such as short preparation cycle, high component structure design, and near-net size molding. This technology mainly uses capillary force to infiltrate molten metal or alloy into the fiber preform. The infiltrated components react chemically with other components in the preform (pyrolytic carbon or resin carbon, etc.) to form a ceramic matrix to prepare a composite material. The main factor affecting the capillary force in this process is the capillary radius. The smaller the radius, the greater the capillary force, which is specifically manifested as the pore size in the fiber preform used. However, Liu et al. (Liu Yue, Research on Preparation of Ultrahigh Temperature Ceramic Modified C / C Composites by Reaction Infiltration, Ph.D. Dissertation of Northwestern Polytechnical University, 2017) found that when using the RMI process to prepare C / C-SiC-ZrB2 composites, high-density composites (low porosity and small pore size) were not conducive to the infiltration of the melt, while low-density composites (high porosity and large pore size) had serious erosion on the original carbon fibers and carbon matrix after melt infiltration, thereby damaging their mechanical properties. At the same time, for composite materials prepared from complex structure preforms, such as 2.5D needle-punched preforms, 3D fine-woven puncture preforms, 3D yarn-wound preforms, three-dimensional four-directional preforms, and mesh-free preforms, there are still large-sized pore structures between the fiber bundles and between the layers. On the one hand, the melt cannot fully react and is lost due to the shortage of carbon source, leaving unfilled pores. On the other hand, a large amount of residual metal will exist inside the composite material, affecting its ablation performance. Therefore, the regulation of the internal pore structure of the composite material is one of the problems that need to be urgently solved to achieve high-efficiency and high-performance reactive infiltration. In addition, Liu et al. (Zhiqiang Liu, Qiangang Fu, Huilun Shi, et al., Comparative study of microstructure and ablation behavior of C / C-HfC-SiC composites prepared under two different conditions, Materials Characterization, 194 (2022) 112467) used RMI technology to prepare C / C-HfC-SiC composites. It can be found that the surface of the material is composed of large-sized ceramic blocks, which are prone to a large number of cracks and other defects due to stress concentration, making it easy for the oxide layer to peel off during the ablation process, and its protective performance cannot be fully exerted.Therefore, how to refine the grains of ceramic particles generated during the infiltration process and alleviate the thermal stress during the ablation process to maintain the stability of the oxide film is still one of the difficulties that RMI technology urgently needs to overcome. Summary of the invention

[0003] In order to avoid the shortcomings of the prior art, the purpose of the present invention is to propose a multi-scale three-dimensional network carbon skeleton structure auxiliary composite material and a preparation method thereof. The present invention aims to introduce a three-dimensional network carbon skeleton structure into a low-density preform composite material, effectively divide the large pores, enhance the capillary action, and at the same time make the molten alloy fully react, reduce the residual metal inside the composite material, and refine the grain size of the ceramic product to prepare a high-performance ceramic-modified composite material.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material, comprising: The low-density fiber preform composite material is impregnated in a precursor solution to obtain an impregnated low-density fiber preform composite material; the precursor solution is a mixture of resorcinol, formaldehyde solution, distilled water and hexadecyltrimethylammonium bromide; The impregnated low-density fiber preform composite material is subjected to a curing treatment, and after the curing is completed, a carbonization treatment is finally performed in a protective atmosphere to form a phenolic resin carbon skeleton structure with a three-dimensional network structure in the low-density fiber preform composite material; The low-density fiber preform composite material that has been subjected to carbonization treatment is subjected to reactive melt infiltration treatment to obtain the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material.

[0005] Preferably, the density of the low-density fiber preform composite material is 1.0-1.3 g / cm 3 .

[0006] Preferably, the low-density fiber preform composite material is a composite material of one or more of a 2.5D needle punched preform, a 3D puncture preform, a 3D winding structure preform, a three-dimensional four-directional preform and a non-web structure preform; The fibers in the low-density fiber preform composite material are one or more of polyacrylonitrile-based carbon fibers, mesophase asphalt-based carbon fibers and SiC fibers.

[0007] Preferably, in the precursor solution, the mass ratio of resorcinol, formaldehyde solution, distilled water and hexadecyltrimethylammonium bromide is (5-8):(7-10):(7-12):(0.05-0.24), and the mass concentration of the formaldehyde solution is 37 wt.%.

[0008] Preferably, when the low-density fiber preform composite material is immersed in the precursor solution, the immersion is carried out at a pressure of 0.01-0.09 MPa for 30-50 min.

[0009] Preferably, when the impregnated low-density fiber preform composite material is cured, it is baked at 60-100° C. for 24-36 hours.

[0010] Preferably, after the curing is completed, the carbonization treatment is finally carried out in a protective atmosphere at 900-1900° C. for 2-4 hours.

[0011] Preferably, when the low-density fiber preform composite material that has been carbonized is subjected to reactive infiltration treatment, the surface of the low-density fiber preform composite material that has been carbonized is covered with alloy compound powder, and then treated in a protective atmosphere at 1800-2000°C for 0.5-2h to obtain the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material.

[0012] Preferably, the alloy compound powder includes at least one of ZrSi2 and HfSi2.

[0013] The present invention also provides a multi-scale three-dimensional network carbon skeleton structure auxiliary composite material, and the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material is prepared by the preparation method of the present invention as described above.

[0014] The present invention has the following beneficial effects: The present invention uses resorcinol and formaldehyde as reaction monomers and CTAB (cetyltrimethylammonium bromide) as a catalyst to prepare a phenolic resin carbon skeleton with a three-dimensional network structure inside a low-density composite material. Figure 1 As shown in the figure, the low-density composite material has a large-sized pore structure inherent in the preform and difficult to be filled with pyrolytic carbon. After the introduction of phenolic resin, the large pores are divided into many three-dimensional small grid structures (see the embodiment of the present invention). Figure 2 , Figure 3 and Figure 4), which enhances the capillary force during the infiltration process and is beneficial to the infiltration of the melt. The introduced three-dimensional network structure of the phenolic resin carbon skeleton has a high specific surface area and can be used as an external carbon source to react with the infiltrated alloy melt to prevent the loss of the melt; at the same time, due to the high specific surface area of ​​the carbon skeleton, more sites are provided, and the carbon skeleton fully reacts with the melt, reducing the metal residue and refining the grain size of the ceramic product generated by the reaction. In the subsequent ablation test, the small-sized ceramic particles weakened the thermal stress during the ablation process, improved the density and stability of the oxide film, and thus improved the ablation resistance of the composite material. The introduced three-dimensional network structure of the phenolic resin carbon skeleton has the advantages of high hardness and strong support. The reaction activity of the carbon skeleton is further controlled by adjusting the carbonization temperature to achieve precise control of the structure of the composite material after infiltration. When the carbonization temperature is low (such as 900 ° C), the carbon skeleton has a low degree of crystallinity, many defects, and a high reaction activity. After fully reacting with the melt, the carbon skeleton is completely converted into ceramics, which plays a role in refining the grain size of the ceramic (see the embodiment of the present invention). Figure 7 ) role; when the carbonization temperature is high (such as 1900 ° C), the carbon atoms are rearranged, the crystallinity of the carbon skeleton is improved, the defects are reduced, and the reactivity is weakened. After fully reacting with the melt, some residual carbon will still exist to form a uniform mosaic structure of "hard carbon-ceramic-pyrolytic carbon" (see the embodiment of the present invention Figure 8 ), compared with the pure ceramic matrix, this structure has two advantages: first, carbon material is the only material that can serve in an environment above 3000 ℃, and the presence of carbon is conducive to maintaining the overall structural stability of the composite material; second, ceramics have the characteristics of high brittleness, and large pieces of ceramics are prone to cracks and other defects. The presence of carbonaceous structure is conducive to the improvement of toughness. Therefore, according to the service environment requirements, the activity of the carbon skeleton is regulated by controlling the carbonization temperature, and the degree of its consumption during the reaction infiltration process is controlled, and finally the precise regulation of the ratio of ceramic to carbon structure in the composite material is achieved. The carbon skeleton structure of the three-dimensional network structure prepared by using resorcinol and formaldehyde has a controllable and adjustable network structure size, that is, by changing the amount of added catalyst CTAB to adjust, it can realize the construction of multi-scale three-dimensional network structures from nanometer to micrometer level, so as to meet the application requirements under different preform structures, different melt properties, and different infiltration conditions. The raw materials used in the preparation process of the present invention are low in price, the preparation process is simple and easy to scale up, and it is not limited by the shape and size of the composite material, and has a strong industrial application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 : Scanning electron microscope image of the three-dimensional network carbon skeleton introduced into the low-density composite material in Example 2 of the present invention; Figure 2 : Scanning electron microscope image of a three-dimensional carbon network skeleton introduced into the interior of a low-density composite material in Example 1 of the present invention; Figure 3 : Scanning electron microscope image of the three-dimensional network carbon skeleton introduced into the low-density composite material in Example 2 of the present invention; Figure 4 : Scanning electron microscope image of the three-dimensional network carbon skeleton introduced into the low-density composite material in Example 3 of the present invention; Figure 5 : Scanning electron microscope image of the three-dimensional network carbon skeleton introduced into the low-density composite material in Comparative Example 1 of the present invention; Figure 6 : Scanning electron microscope image of the three-dimensional network carbon skeleton introduced into the low-density composite material in Comparative Example 2 of the present invention; Figure 7 : Scanning electron microscope image of the composite material after reaction infiltration in Example 1 of the present invention; Figure 8 : Scanning electron microscope image of the composite material after reaction infiltration in Example 2 of the present invention; Fig. 9 : Scanning electron microscope image of the composite material after reaction infiltration in Example 3 of the present invention; Fig.10 : Scanning electron microscope image of the composite material after reaction infiltration in Comparative Example 1 of the present invention; Fig.11 : Scanning electron microscope image of the composite material after reaction infiltration in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0017] Based on the two major challenges faced by RMI technology, the present invention introduces a carbonaceous material with a high specific surface area and a strong supporting structure into the composite material to achieve a full reaction to the molten alloy, reduce residual metal, and refine the grain size of the generated ceramic, thereby solving the difficult problems faced by RMI technology. The present invention introduces a carbon skeleton structure with three-dimensional network characteristics into a low-density carbon fiber preform composite material, effectively dividing the large pores inside the composite material into a small network structure, so as to assist the reaction infiltration technology in preparing a high-performance ceramic-modified composite material. The specific scheme of the present invention is as follows.

[0018] The method for preparing the multi-scale three-dimensional network carbon skeleton structure-assisted composite material of the present invention comprises the following steps: Step 1: Prepare a precursor solution: stir 5-8 g of resorcinol, 7-10 g of formaldehyde solution and 7-12 g of distilled water for 30-50 min to obtain a mixed solution, then add 0.05-0.24 g of hexadecyltrimethylammonium bromide (CTAB) as a catalyst to the mixed solution, continue stirring for 20-40 min to obtain a precursor solution; Wherein, the mass concentration of the formaldehyde solution is 37 wt.%; Step 2: Low-density fiber preform composite material impregnation: impregnate the preform with a density of 1.0-1.3 g / cm 3 The low-density fiber preform composite material (hereinafter referred to as low-density composite material) is immersed in the precursor solution prepared in step 1, and then placed in a vacuum box and immersed for 30-50 min at a pressure of 0.01-0.09 MPa; wherein the low-density fiber preform includes one or more composite materials selected from 2.5D needle punched preform, 3D puncture preform, 3D winding yarn structure preform, three-dimensional four-directional preform and non-web tire structure preform; the low-density preform can be prepared using polyacrylonitrile-based carbon fiber, mesophase asphalt-based carbon fiber and SiC fiber; Step 3: Curing and carbonization: The impregnated composite material obtained in step 2 is placed in an oven at 60-100°C for 24-36 hours of curing treatment, and then the cured composite material is placed in a tubular furnace at 900-1900°C for heat treatment under a protective atmosphere for 2-4 hours for carbonization, wherein the tubular furnace is an argon atmosphere with an argon flow rate of 2-4 L / min; after carbonization, a phenolic resin carbon skeleton structure with a three-dimensional network structure is prepared in the low-density fiber preform composite material; Step 4: Reaction infiltration treatment: Place the composite material with the three-dimensional carbon skeleton structure obtained in step 3 in a graphite crucible, cover the surface with alloy compound powder, and then place the graphite crucible in a heat treatment furnace at 1800-2000 ° C for 0.5-2 h to finally prepare a composite material modified by ceramic, i.e., a multi-scale three-dimensional network carbon skeleton structure auxiliary composite material of the present invention. The alloy compound powder includes one or two of ZrSi2 and HfSi2, and the heat treatment furnace is an argon atmosphere with an argon flow rate of 8-10 L / min.

[0019] Embodiment 1: The method for preparing the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material of this embodiment comprises the following steps: Step 1: 5 g of resorcinol, 7 g of formaldehyde solution and 7 g of distilled water were stirred for 30 min to obtain a mixed solution, and then 0.05 g of hexadecyltrimethylammonium bromide was added to the mixed solution as a catalyst, and the mixture was stirred for 20 min to obtain a precursor solution. Step 2: Set the density to 1.0 g / cm 3 The 3D low-density composite material with polyacrylonitrile-based carbon fiber as reinforcement is immersed in the precursor solution prepared in step 1, placed in a vacuum box, and immersed for 30 minutes at a pressure of 0.01 MPa; Step 3: placing the impregnated composite material obtained in step 2 in an oven at 60°C for 36 hours of curing treatment, and then placing the cured composite material in a tubular furnace at 900°C for 4 hours of heat treatment for carbonization, wherein the tubular furnace is an argon atmosphere with an argon flow rate of 2 L / min; after carbonization, a phenolic resin carbon skeleton structure with a three-dimensional network structure is prepared in the low-density fiber preform composite material, and the pore structure of the prepared carbon skeleton is 20-25 μm; Step 4: Place the composite material with a three-dimensional carbon skeleton structure obtained in step 3 in a graphite crucible, cover its surface with HfSi2 powder, and then place the graphite crucible in a heat treatment furnace at 1800°C for 2 h. The heat treatment furnace is an argon atmosphere with a flow rate of 8 L / min, and finally a ceramic-modified composite material is prepared.

[0020] The results show that the macropores inside the low-density C / C composites are filled with a three-dimensional network of carbon skeletons formed by stacking of small spherical particles (e.g. Figure 2 As shown in the figure, the pore size of the skeleton is 20-25 μm. After reactive infiltration, the pores in the low-density C / C are filled with ceramic particles. The grain size of the ceramic particles is small and evenly distributed. Figure 7 The black part is the unreacted carbon, the gray part is the SiC phase, and the white part is the HfC phase. 2 After high-flow oxyacetylene ablation, the mass ablation rate and line ablation rate are only -0.63 mg / s and 3.47 μm / s, showing excellent anti-ablation performance.

[0021] Embodiment 2: The method for preparing the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material of this embodiment comprises the following steps: Step 1: 8 g of resorcinol, 10 g of formaldehyde solution and 10 g of distilled water were stirred for 50 min to obtain a mixed solution, and then 0.14 g of hexadecyltrimethylammonium bromide was added to the mixed solution as a catalyst, and the mixture was stirred for 40 min to obtain a precursor solution. Step 2: Set the density to 1.3 g / cm 3 The 2.5D low-density composite material with polyacrylonitrile-based carbon fiber as reinforcement is immersed in the precursor solution prepared in step 1, placed in a vacuum box, and immersed for 50 minutes at a pressure of 0.09 MPa; Step 3: placing the impregnated composite material obtained in step 2 in an oven at 100°C for 24 hours of curing treatment, and then placing the cured composite material in a heat treatment furnace at 1900°C for 2 hours for carbonization, wherein the tubular furnace is an argon atmosphere with an argon flow rate of 4 L / min; after carbonization, a phenolic resin carbon skeleton structure with a three-dimensional network structure is prepared in the low-density fiber preform composite material, and the pore structure of the prepared carbon skeleton is 10-15 μm; Step 4: Place the composite material with a three-dimensional carbon skeleton structure obtained in step 3 in a graphite crucible, cover its surface with ZrSi2 powder, and then place the graphite crucible in a heat treatment furnace at 2000°C for 0.5 h. The heat treatment furnace is an argon atmosphere with a flow rate of 10 L / min, and finally a ceramic-modified composite material is prepared.

[0022] The results show that the macropores in the low-density C / C composites are filled with a three-dimensional network of carbon skeletons (e.g. Figure 3 As shown in the figure, the pore size of the skeleton is 10-15 μm; after reactive infiltration, the pores in the low-density C / C are filled with ceramic particles, and the grain size of the ceramic particles is small and evenly distributed, among which, Figure 8 The black part is the unreacted carbon, the gray part is the SiC phase, and the white part is the ZrC phase. 2 After high-flow oxyacetylene ablation, the mass ablation rate and line ablation rate were only -0.42 mg / s and 3.56 μm / s, showing excellent anti-ablation performance.

[0023] Embodiment 3: The method for preparing the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material of this embodiment comprises the following steps: Step 1: 7 g of resorcinol, 9 g of formaldehyde solution and 12 g of distilled water were stirred for 40 min to obtain a mixed solution, and then 0.24 g of hexadecyltrimethylammonium bromide was added to the mixed solution as a catalyst, and the mixture was stirred for 30 min to obtain a precursor solution. Step 2: Set the density to 1.2 g / cm 3 The 2.5D low-density composite material with polyacrylonitrile-based carbon fiber as reinforcement is immersed in the precursor solution prepared in step 1, placed in a vacuum box, and immersed for 40 minutes at a pressure of 0.05 MPa; Step 3: placing the impregnated composite material obtained in step 2 in an oven at 80°C for 34 hours of curing treatment, and then placing the cured composite material in a tubular furnace at 1100°C for heat treatment for 3 hours for carbonization, wherein the tubular furnace is an argon atmosphere with an argon flow rate of 3 L / min; after carbonization, a phenolic resin carbon skeleton structure with a three-dimensional network structure is prepared in the low-density fiber preform composite material, and the pore structure of the prepared carbon skeleton is 5-8 μm; Step 4: Place the composite material with a three-dimensional carbon skeleton structure obtained in step 3 in a graphite crucible, cover its surface with ZrSi2 powder, and then place the graphite crucible in a heat treatment furnace at 1900°C for 1 h. The heat treatment furnace is an argon atmosphere with a flow rate of 9 L / min, and finally a ceramic-modified composite material is prepared.

[0024] The results show that the macropores in the low-density C / C composites are filled with a three-dimensional network of carbon skeletons (e.g. Figure 4 As shown in the figure, the pore size of the skeleton is 5-8 μm. After reactive infiltration, the pores in the low-density C / C are filled with ceramic particles. The grain size of the ceramic particles is small and evenly distributed. Fig. 9 The black part is the unreacted carbon, the gray part is the SiC phase, and the white part is the ZrC phase. 2 After high-flow oxyacetylene ablation, the mass ablation rate and line ablation rate were only -0.48 mg / s and 3.77 μm / s, showing excellent anti-ablation performance.

[0025] Comparative Example 1: The preparation method of the composite material of this comparative example comprises the following steps: Step 1: 8 g of resorcinol, 10 g of formaldehyde solution and 18 g of distilled water were stirred for 50 min to obtain a mixed solution, and then 0.14 g of hexadecyltrimethylammonium bromide was added to the mixed solution as a catalyst, and the mixture was stirred for 40 min to obtain a precursor solution. Step 2: Set the density to 1.3 g / cm 3 The 2.5D low-density composite material with polyacrylonitrile-based carbon fiber as reinforcement is immersed in the precursor solution prepared in step 1, placed in a vacuum box, and immersed for 50 minutes at a pressure of 0.09 MPa; Step 3: placing the impregnated composite material obtained in step 2 in an oven at 100°C for 24 h for curing, and then placing the cured composite material in a heat treatment furnace at 1900°C for 2 h for carbonization, wherein the tubular furnace is an argon atmosphere with an argon flow rate of 4 L / min; Step 4: Place the composite material obtained in step 3 in a graphite crucible, cover its surface with ZrSi2 powder, and then place the graphite crucible in a heat treatment furnace at 2000 °C for 0.5 h. The heat treatment furnace is an argon atmosphere with a flow rate of 10 L / min, and finally a ceramic-modified composite material is prepared.

[0026] Depend on Figure 5 It can be seen that the composite material has not been introduced into the interior of the three-dimensional network carbon skeleton structure, and the obtained spherical carbon structure is discontinuously distributed. Compared with the three-dimensional network structure, this structure fails to make the melt and the introduced carbon fully react during infiltration, resulting in the formation of ceramic products with continuous large pieces and many cracks and defects (such as Fig.10 ), 4.2MW / m 2 After high-flow oxyacetylene ablation, the mass ablation rate and the line ablation rate were -1.76 mg / s and 4.98 μm / s, respectively. Compared with Example 2, the ablation resistance was poor. Comparative Example 2: The preparation method of the composite material of this comparative example comprises the following steps: Step 1: 8 g of resorcinol, 10 g of formaldehyde solution and 25 g of distilled water were stirred for 50 min to obtain a mixed solution, and then 0.14 g of hexadecyltrimethylammonium bromide was added to the mixed solution as a catalyst, and the mixture was stirred for 40 min to obtain a precursor solution. Step 2: Set the density to 1.3 g / cm 3 The 2.5D low-density composite material with polyacrylonitrile-based carbon fiber as reinforcement is immersed in the precursor solution prepared in step 1, placed in a vacuum box, and immersed for 50 minutes at a pressure of 0.09 MPa; Step 3: placing the impregnated composite material obtained in step 2 in an oven at 100°C for 24 h for curing, and then placing the cured composite material in a heat treatment furnace at 1900°C for 2 h for carbonization, wherein the tubular furnace is an argon atmosphere with an argon flow rate of 4 L / min; Step 4: Place the composite material obtained in step 3 in a graphite crucible, cover its surface with ZrSi2 powder, and then place the graphite crucible in a heat treatment furnace at 2000 °C for 0.5 h. The heat treatment furnace is an argon atmosphere with a flow rate of 10 L / min, and finally a ceramic-modified composite material is prepared.

[0027] Depend on Figure 6It can be seen that the composite material has not been introduced into the interior of the carbon skeleton structure with a three-dimensional network, and the obtained carbon structure is a discontinuously distributed large spherical structure. Compared with the three-dimensional network structure, this structure fails to make the melt and the introduced carbon fully react during infiltration, resulting in the formation of ceramic products with continuous large pieces and many cracks and defects (such as Fig.11 As shown), 4.2 MW / m 2 After high-flow oxyacetylene ablation, the mass ablation rate and the line ablation rate were -1.56 mg / s and 4.23 μm / s, respectively. Compared with Example 2, the ablation resistance was poor.

[0028] The specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material, characterized in that: include: impregnating the low-density fiber preform composite material in a precursor solution to obtain an impregnated low-density fiber preform composite material; The precursor solution is a mixture of resorcinol, formaldehyde solution, distilled water and hexadecyltrimethylammonium bromide; The impregnated low-density fiber preform composite material is subjected to a curing treatment, and after the curing is completed, a carbonization treatment is finally performed in a protective atmosphere to form a phenolic resin carbon skeleton structure with a three-dimensional network structure in the low-density fiber preform composite material; The low-density fiber preform composite material that has been subjected to carbonization treatment is subjected to reactive melt infiltration treatment to obtain the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material.

2. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: The density of the low-density fiber preform composite material is 1.0-1.3 g / cm 3 .

3. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: The low-density fiber preform composite material is a composite material of one or more of a 2.5D needle-punched preform, a 3D puncture preform, a 3D winding structure preform, a three-dimensional four-directional preform and a non-web structure preform; The fibers in the low-density fiber preform composite material are one or more of polyacrylonitrile-based carbon fibers, mesophase asphalt-based carbon fibers and SiC fibers.

4. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: In the precursor solution, the mass ratio of resorcinol, formaldehyde solution, distilled water and hexadecyltrimethylammonium bromide is (5-8): (7-10): (7-12): (0.05-0.24), and the mass concentration of the formaldehyde solution is 37 wt.%.

5. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: When the low-density fiber preform composite material is impregnated in the precursor solution, the impregnation is carried out at a pressure of 0.01-0.09 MPa for 30-50 minutes.

6. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: When the impregnated low-density fiber preform composite material is cured, it is baked at 60-100° C. for 24-36 hours.

7. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: After the curing is completed, the carbonization treatment is finally carried out in a protective atmosphere at 900-1900 ℃ for 2-4 hours.

8. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 1, characterized in that: When the low-density fiber preform composite material that has been carbonized is subjected to reactive infiltration treatment, the surface of the low-density fiber preform composite material that has been carbonized is covered with alloy compound powder, and then treated in a protective atmosphere at 1800-2000°C for 0.5-2h to obtain the multi-scale three-dimensional network carbon skeleton structure auxiliary composite material.

9. The method for preparing a multi-scale three-dimensional network carbon skeleton structure-assisted composite material according to claim 8, characterized in that: The alloy compound powder includes at least one of ZrSi2 and HfSi2.

10. A multi-scale three-dimensional network carbon skeleton structure auxiliary composite material, characterized in that: The multi-scale three-dimensional network carbon skeleton structure auxiliary composite material is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method for fiber-reinforced superhigh temperature ceramic matrix composite

    CN103964882A

  • Preparation method of C / SiC composite material

    CN108892524A

  • Method for filling activated carbon in carbon fiber preform and application thereof

    CN109180210A

  • Porous carbon-assisted ZrC modified C / C composite material and preparation method thereof

    CN118420374A

  • Method for preparing a carbide ceramics multilayer coating on, and optionally in, a part made of a carbon-containing material using a reactive melt infiltration RMI technique

    US20160040299A1

Cited By

  • 2.5 D woven ceramic-based composite material based on C / C composite material and preparation method of 2.5 D woven ceramic-based composite material

    CN120518403A

  • A low-density high-strength carbon / carbon composite material and a method for preparing the same

    CN123003307A